PENERAPAN MANAJEMEN RISIKO UNTUK BANK - Riffa Haviani Laluma (Jurnal Computech & Bisnis (e-Journal), 2015)
Information technology is a component of the success of the bank to measure the success rate of information in order to improve the performance and competitiveness of banking. Banking information technology requires a high standardization especially for security , data integrity, delivary service. Therefore banking risk management to be very crucial. According to industry standards for risk management ( Basel II ), the bank must manage operational risk in addition to credit risk and market risk, operational risk mentioned in the risk management standards which consists of 7 types of events that employment practices and workshop safety, clients, products and business practices, business disruption and system failure, execution, delivery and process management, damage to physical assets, internal fraud and external fraud. The results of this analysis show that the bank is not in full compliance in accordance with the standardization of Basel II because of problems managed only problem transactions core banking application system that has a high frequency but low risk. Banks are also not applying operational risk management information technology. So that needs to produce IT operational risk management consists of risk identification, risk evaluation, risk response, safeguards. Keywords: Basel, Safeguard Abstrak Teknologi Informasi merupakan komponen keberhasilan bank untuk pengukuran tingkat keberhasilan informasi dalam rangka meningkatkan kinerja dan daya saing perbankan. TeknoIogi Informasi perbankan memerlukan suatu standarisasi yang tinggi khususnya untuk keamanan, integritas data, delivary service. Karena itu manajemen resiko untuk perbankan menjadi sangat krusial. Menurut standar industri untuk manajemen risiko (Basel II), bank harus mengelola risiko operasional disamping  risiko kredit dan risiko pasar, risiko operasional yang disebutkan pada standar manajemen risiko yang terdiri atas 7 tipe peristiwa yaitu employment prctices & workshop safety, client, products & business practice, business disruption & system failure, execution delivery & process management, damage to physical assets, internal fraud dan external fraud. Hasil analisa ini memperlihatkan bahwa bank belum compliance secara penuh sesuai dengan standarisasi dari Basel II karena permasalahan yang dikelola hanyalah permasalahan transaksi sistem aplikasi core banking yang memiliki frekuensi tinggi namun risiko kecil. Bank juga belum menerapkan manajemen risiko operasional teknologi informasi. Sehingga perlu menghasilkan manajemen risiko operasional TI yang terdiri dari identifikasi risiko, evaluasi risiko, respon risiko, safeguard. Keywords : Basel, safeguard